Analisis Gaya Kepemimpinan Lurah Terhadap Kualitas Pelayanan Publik Di Kelurahan Cempa Kecamatan Cempa Kabupaten Pinrang - Nanda Putri Amalia; Andi Uceng; Hardianti Hardianti (Science and Education Journal (SICEDU), 2026)
This study aims to analyze the leadership style of village heads and its influence on the quality of public services at the Cempa Village Office, Cempa District, Pinrang Regency. The focus of this research includes the implementation of leadership style and its impact on the quality of services provided to the community.This study employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving informants selected purposively. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing, with the assistance of NVivo 12 software to perform coding and systematically visualize relationships between variables.The research results show that village head leadership styles tend to be democratic and participatory, characterized by open communication and staff involvement in decision-making. This leadership style has a positive impact on the quality of public services, although several obstacles remain in its implementation. Therefore, village head leadership styles need to be continuously improved to achieve better and more optimal public servic